Response of maize (Zea mays L.) ikenne variety to application of household urban solid wastes compost - Alate, KKA; Mawussi, G; Ayisah, KD; Sanda, K (International Journal of Agricultural Research, Innovation and Technology, 2020)
Soils fertility declining limits agricultural production in Togo where maize (Zea mays L.) is most cereal cropping and base staple food. Currently, mineral fertilizers are beyond the reach of farmers due to high price and limited availability. This study assessed the response of household urban wastes compost to the growth and yield of maize Ikenne variety. Experiments were performed in rainy season of years 2018 and 2019 at Teaching Research and Demonstration Farm of Agronomy School in University of Lome, Togo. Agronomic trials were set at randomized in complete block design with three replications, where control plots, compost plots at different doses and mineral fertilizers plots constituted the treatments. The growth parameters, including plant height, stem girth, leaf area and number of leaves per plant, were measured at the milky maize stage. The yield parameters, including length and girth of cob, thousand grains weight, grain yield and straw yield, were collected at harvesting. Data were statistically analyzed. The results showed three distinct homogeneous groups of treatments both for growth and yield parameters. Plots treated with compost at 30 t ha-1 and 40 t ha-1 constitute the best group, which differs significantly from the second group formed by plots treated with compost at 10 t ha-1 and 20 t ha-1 and mineral fertilizer plots. Control treatments constitute the last group. Growth and yield parameters values increase with compost dose. Far from being used alone in place of mineral conventional fertilizer, integrated fertilization based on combination of mineral fertilizer and compost of household urban wastes will investigated in maize cropping in southern Togo for optimal compost dose to recommend. Int. J. Agril. Res. Innov. Tech. 10(1): 97-101, June 2020